2004
DOI: 10.1074/jbc.m405486200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cell Surface HSP90 in Cell Migration Reveals a Novel Role in the Developing Nervous System

Abstract: Heat shock protein HSP90 plays important roles in cellular regulation, primarily as a chaperone for a number of key intracellular proteins. We report here that the two HSP90 isoforms, ␣ and ␤, also localize on the surface of cells in the nervous system and are involved in their migration. A 94-kDa surface antigen, the 4C5 antigen, which was previously shown to be involved in migration processes during development of the nervous system, is shown to be identical to HSP90␣ using mass spectrometry analysis. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
97
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 51 publications
7
97
0
3
Order By: Relevance
“…However, because of lack of adequate mono-specific anti-Hsp90a and Hsp90b antibodies for FACS and IF, we are unable to state whether Hsp90a, in addition to Hsp90b, is also expressed at the SH-SY5Y cell surface. Cell surface Hsp90 (a/b) expression was also detected in pcDNA and TrkAIII transfectants, adding SH-SY5Y cells to other tumour and normal cell types that express cell surface Hsp90 (a/b) (Becker et al, 2004;Sidera et al, 2004Sidera et al, , 2008 and TrkAI to other cell surface receptors that depend on interaction with Hsp90 for stability (Vega and De Maio, 2003;Peng et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…However, because of lack of adequate mono-specific anti-Hsp90a and Hsp90b antibodies for FACS and IF, we are unable to state whether Hsp90a, in addition to Hsp90b, is also expressed at the SH-SY5Y cell surface. Cell surface Hsp90 (a/b) expression was also detected in pcDNA and TrkAIII transfectants, adding SH-SY5Y cells to other tumour and normal cell types that express cell surface Hsp90 (a/b) (Becker et al, 2004;Sidera et al, 2004Sidera et al, , 2008 and TrkAI to other cell surface receptors that depend on interaction with Hsp90 for stability (Vega and De Maio, 2003;Peng et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Cell surface expression of Hsp90 has been observed on melanoma cells, fibrosarcoma cells and neuronal cells (Erkeller-Yuksel et al, 1992;Becker et al, 2004;Eustace et al, 2004;Sidera et al, 2004). In melanoma cells, cell surface Hsp90 expression correlates positively with metastatic potential (Becker et al, 2004), and inhibition of cell surface Hsp90 with antibody (Sidera et al, 2004) or GA coupled to cell-impermeable agarose beads (Eustace et al, 2004) has been reported to reduce cell migration in vitro. Thus, cell surface Hsp90 may play a role in cancer cell motility and metastasis distinct from but perhaps overlapping with its intracellular chaperone function.…”
Section: Introductionmentioning
confidence: 99%
“…For example, GRP78 was first identified at the surface of malignant lymphocytes (17), and the elevated levels observed on the surface of malignant cells have been exploited to successfully target and kill these cells with small molecules (18,19). GRP94 is similarly detected at the membrane in the nervous system, where it was found to regulate cell migration (20).…”
mentioning
confidence: 99%